Spectrum of ocular manifestations among bus drivers and conductors - Suresh Dhage, Vaishnavi; Bellary, Radhika C.; Ramesh, Lavanya Sriram; Chandaki, Akshata; Channashetti, Gajanan D. (International Journal Of Community Medicine And Public Health, 2025)
Background: Bus drivers and conductors rely heavily on good vision for safe and efficient transport. Prolonged exposure to environmental stress, irregular schedules, and limited access to eye care increase their risk of developing ocular issues. This study aims to assess the prevalence and types of ocular manifestations in this group to highlight the need for regular eye examinations and timely treatment. Methods: Study was carried out in Gadag city among 75 bus drivers and conductors. Basic personal details and history regarding ophthalmic complaints were taken. Complete ocular examination was carried out. Patients with refractive error were given spectacle correction. Few who needed medical management were treated accordingly. Results: Majority of them were males (81.3%).14.6% had dry eye symptoms. 46.6% of them were presbyopic. Surgical management was required in 22.6% patients (cataract and pterygium). Allergic eye disease was seen in 5.3% patients. systemic illness like diabetes and hypertension was seen in 6 patients. Conclusions: Regular eye examination and intervention whenever needed promotes good eye health of the bus drivers and conductors and even helps in efficient public transport.